Assessing positional accuracy of drainage networks extracted from ASTER, SRTM and OpenStreetMap - Monteiro, Elisabete (2016)
This study intends to evaluate the positional accuracy and compare the completeness of the drainage networks extracted from three sources of free geographic data, namely from the Digital Elevation Models ASTER and SRTM and the collaborative project OpenStreetMap (OSM), in an area included in the basin of Mondego river, located in the centre of continental Portugal. The drainage networks extracted from ASTER and SRTM are generated considering several values of flow accumulation as the critical level to identify the water courses and the feature “waterway” was extracted from OSM. To assess the completeness and positional accuracy of these water courses the drainage network of the 1/25000 topographic map of the Portuguese Army Geographical Institute was used as reference. The distance between the ASTER, SRTM and OSM derived water courses to the reference data was computed as well as the length of the water courses and the results compared.